"The Good, the Bad and the Ugly" Reconsidered: A Comparison of German, Canadian and Spanish Labour Migration Policies. Issue 1 (1st January 2017) - Finotelli, Claudia; Kolb, Holger
Abstract: This article compares three immigration countries that are perceived, both publicly and politically, as being fundamentally different: Canada, which is allegedly one of the most attractive destination countries for labour migrants worldwide; Germany, which is still thought to be sceptical towards immigration; and finally Spain, which is considered institutionally incapable of implementing efficient labour migration policies. Against the backdrop of various political reforms that have been adopted in these countries, however, the article argues that such a distinction is becoming increasingly inaccurate. This observation is backed empirically by analysing the technique of screening labour migrants and the temporal design of labour migration policy.